Recovirus NS1-2 Has Viroporin Activity That Induces Aberrant Cellular Calcium Signaling To Facilitate Virus Replication - Alicia C. Strtak (American Society for Microbiology, 2019)
ABSTRACT Enteric viruses in the Caliciviridae family cause acute gastroenteritis in humans and animals, but the cellular processes needed for virus replication and disease remain unknown. A common strategy among enteric viruses, including rotaviruses and enteroviruses, is to encode a viral ion channel (i.e., viroporin) that is targeted to the endoplasmic reticulum (ER) and disrupts host calcium (Ca2+) homeostasis. Previous reports have demonstrated genetic and functional similarities between the nonstructural proteins of caliciviruses and enteroviruses, including the calicivirus NS1-2 protein and the 2B viroporin of enteroviruses. However, it is unknown whether caliciviruses alter Ca2+ homeostasis for virus replication or whether the NS1-2 protein has viroporin activity like its enterovirus counterpart. To address these questions, we used Tulane virus (TV), a rhesus enteric calicivirus, to examine Ca2+ signaling during infection and determine whether NS1-2 has viroporin activity that disrupts Ca2+ homeostasis. We found that TV increases Ca2+ signaling during infection and that increased cytoplasmic Ca2+ levels are important for efficient replication. Further, TV NS1-2 localizes to the endoplasmic reticulum, the predominant intracellular Ca2+ store, and the NS2 region has characteristics of a viroporin domain (VPD). NS1-2 had viroporin activity in a classic bacterial functional assay and caused aberrant Ca2+ signaling when expressed in mammalian cells, but truncation of the VPD abrogated these activities. Together, our data provide new mechanistic insights into the function of the NS2 region of NS1-2 and support the premise that enteric viruses, including those within Caliciviridae, exploit host Ca2+ signaling to facilitate their replication. IMPORTANCE Tulane virus is one of many enteric caliciviruses that cause acute gastroenteritis and diarrheal disease. Globally, enteric caliciviruses affect both humans and animals and amass >65 billion dollars per year in treatment and health care-associated costs, thus imposing an enormous economic burden. Recent progress has resulted in several cultivation systems (B cells, enteroids, and zebrafish larvae) to study human noroviruses, but mechanistic insights into the viral factors and host pathways important for enteric calicivirus replication and infection are still largely lacking. Here, we used Tulane virus, a calicivirus that is biologically similar to human noroviruses and can be cultivated by conventional cell culture, to identify and functionally validate NS1-2 as an enteric calicivirus viroporin. Viroporin-mediated calcium signaling may be a broadly utilized pathway for enteric virus replication, and its existence within caliciviruses provides a novel approach to developing antivirals and comprehensive therapeutics for enteric calicivirus diarrheal disease outbreaks.